Fatores de risco para complicações pós-operatórias e mortalidade hospitalar em idosos submetidos a tratamento cirúrgico de fraturas de fêmur proximal - Soares, Danielle Cristina de Oliveira (2023)
The increase in life expectancy that has occurred in recent decades around the world has caused the number of cases of elderly people over 60 years old who fall from their own height with subsequent fracture of the proximal femur to increase. The objective of this study was to identify the risk factors associated with postoperative complications and hospital mortality in elderly people undergoing surgical treatment for proximal femur fracture in a tertiary trauma reference hospital in Fortaleza-CE. An observational, analytical study was carried out, a retrospective cohort consisting of elderly people undergoing surgical interventions from 10/01/2019 to 10/31/2021. The association between demographic and clinical characteristics and the occurrence of postoperative complications and in-hospital death were assessed using univariate and multivariate analyses, with the strength of the association measured by the odds ratio (OR) and its respective confidence interval 95% (95%CI). The cohort consisted of 809 patients, of whom 339 underwent intracapsular surgical interventions and 470 extracapsular operations. The median age was 80 years (60-106), with a predominance of females (68.48%). In the analysis of postoperative complications, it was found that males (OR=1.53; 95%CI: 1.08 – 2.18; P=0.0174), ages greater than or equal to 80 years (OR =1.62; 95%CI: 1.14 – 2.31; P=0.0078), having chronic obstructive pulmonary disease (OR=2.56; 95%CI: 1.20 – 5.46; P=0.0153), the occurrence of pneumonia (OR=2.04; 95%CI: 1.10 – 3.77; P=0.0230) and psychomotor agitation (OR=2.27; 95%CI: 1.40 – 3.69; P=0.0009) in the preoperative period and intracapsular surgical procedures (OR=1.63; 95%CI: 1.15 – 2.31; P=0.0057) are predictors of the occurrence of complications postoperative. The hospital mortality rate for proximal femur surgical procedures was 6.43% (95%CI: 4.94 – 8.33). It was also found that the occurrence of pneumonia (OR=3.46; 95%CI: 1.23 – 9.73; P=0.0188) and psychomotor agitation (OR=3.83; 95%CI: 1.55 – 9.47; P=0.0037) in the preoperative period, the occurrence of pneumonia (OR=9.48; 95%CI: 3.90 – 23.06; P<0.0001), tract infection urinary tract (OR=3.21; 95%CI: 1.005 – 10.24; P=0.0490) and acute renal failure (OR=6.18; 95%CI: 2.64 – 14.45; P<0.0001) in the postoperative period and unplanned admission to the ICU in the postoperative period (OR=11.45; 95%CI: 4.33 – 30.30; P<0.0001) constituted independent factors associated with the occurrence of hospital death. These findings demonstrate the need for greater attention to elderly people aged 80 years or over, male, with chronic lung disease and who undergo intracapsular surgical interventions, as they are more likely to develop postoperative complications, as well as strict surveillance regarding the occurrence of nosocomial infections, notably those of the lower respiratory tract, given that they greatly increase the risk of hospital death.